Hydrodynamic ram ballistic limit analysis of aluminium tank / Mohd Rozaiman Aziz - Aziz, Mohd Rozaiman (Institute of Graduate Studies, UiTM, 2017)
This thesis presents the ballistic impact study for the non-filled and waterfilled aluminium tank. This study combined the ballistic limit (BL) and hydrodynamic ram (HRAM) together. Previously, these two areas were not cross-field. Researchers in BL concentrated on determination of the minimum velocity to perforate a target. Common targets are single plate and double plates either in contact or has a space/air in between. There is less study by using double plates with water in between as the target. Meanwhile in HRAM study, many researchers are concentrated on pressure-time history. Less attention was given towards minimum velocity to perforate target. It is important to determine the BL in HRAM study, otherwise the target will not perforate. As a result, pressure-time history cannot be obtained. The main objective of this research is to investigate the BL in HRAM of an (water-filled) aluminium tank, experimentally and numerically (simulation). Meanwhile the specific objectives of this study are to determine the BL and carry-out HRAM investigation thru experiment associate with analytical model, to develop finite element model for BL and smoothed particle hydrodynamics (SPH) model for HRAM simulation and to validate the mode of failure and wall deformation obtained from simulation with experimental results. The tank was impacted with fragment simulating projectile (FSP) with velocities ranging from 239 m/s up to 972 m/s (experiment) and 2000 m/s (numerical simulation). The aluminium tank was 3 mm thick, 150 mm wide and 750 mm long…